Giant complicated ureterocele in a female infant - Mutua Irene; Jumbi Tim; John Rodrigues; Denver Mariga; Swaleh Shahbal; Peter Mwika; Kihiko Kuria; Francis Osawa; Kebuka Caroline; Mulama Beatrice; Nyabanda Rose; Francis Ndiangui; et al. (Elsevier, 2020)
Ureterocele is defined as a cystic dilatation of the terminal ureter. It is associated with obstructive uropathy, recurrent urinary tract infections, and acute/chronic renal injury. We present a case of a single system giant ureterocele at the bladder neck in an 8-month-old female infant that presented with an abdominal mass, pus discharge per urethra and failure to thrive. The aim is to highlight an unusual presentation of a giant ectopic left ureterocele in a female infant.